+20

1 year ago

Mathematics

High School

Answer:

y = - (x - 3)² + 15

Step-by-step explanation:

using the method of completing the square

y = x² + 6x + 6 ← factor out - 1 from the first 2 terms

y = - (x² - 6x) + 6

to complete the square

add/subtract ( half the coefficient of the x- term )² to x² - 6x

y = - (x² + 2(- 3)x + 9 - 9) + 6

= - (x - 3)² + 9 + 6

= - (x - 3)² + 15

Forgot your password?

Don't have an account? Sign up!

or go back to login page

Answer:y = - (x - 3)² + 15

Step-by-step explanation:using the method of completing the square

y = x² + 6x + 6 ← factor out - 1 from the first 2 terms

y = - (x² - 6x) + 6

to complete the square

add/subtract ( half the coefficient of the x- term )² to x² - 6x

y = - (x² + 2(- 3)x + 9 - 9) + 6

= - (x - 3)² + 9 + 6

= - (x - 3)² + 15